(untitled) (Fiep Bulletin - online, 2014)
The objective of this study was to analyze the perspective of 139 students of the Physical Education Course at ULBRA regarding the Supervised Internship in Physical Education (I, II, III, IV and the old internship) for their teacher training. A questionnaire was used composed of open and closed questions with data obtained classified in categories of analysis elaborated a priori. It was noted that 77% of the collaborating subjects belonged to the old curriculum, before 2004, and these students were found to have taken subjects outside of the curricular grid and stated that they felt prepared for the internship, although 31% related to be unprepared for this practice. It is believed, with this research, that debate and reflection on the practice of teaching can be encouraged.